Analgesic, Anti-Inflammatory and Anticancer Activities of Extra Virgin Olive Oil. (22nd December 2013) - Fezai, Myriam; Senovilla, Laura; Jemaà, Mohamed; Ben-Attia, Mossadok
Abstract : Background . In folk medicine, extra virgin olive oil (EVOO) is used as a remedy for a variety of diseases. This study investigates the in vivo antinociceptive, anti-inflammatory, and anti-cancer effects of EVOO on mice and rats. Materials and Methods . In this experimental study, using the acetic acid-induced writhing and formalin tests in mice, the analgesic effect of EVOO was evaluated. Acetylsalicylic acid and morphine were used as standard drugs, respectively. The anti-inflammatory activity was investigated by means of the carrageenan-induced paw edema model in rats using acetylsalicylic acid and dexamethasone as standard drugs. Last, the xenograft model in athymic mice was used to evaluate the anticancer effect in vivo . Results . EVOO significantly decreased acetic acid-induced abdominal writhes and reduces acute and inflammatory pain in the two phases of the formalin test. It has also a better effect than Dexamethasone in the anti-inflammatory test. Finally, the intraperitoneal administration of EVOO affects the growth of HCT 116 tumours xenografted in athymic mice. Conclusion . EVOO has a significant analgesic, anti-inflammatory, and anticancer properties. However, further detailed studies are required to determine the active component responsible for these effects and mechanism pathway.